Revamping the Ophthalmic Clinical Practice during Pandemic Covid 19; A Potential New Normal: Doi: 10.36351/pjo.v37i4.1279 - Hayat, Nausheen; Sarhandi, Saad Jaan; Cheema, Alyscia (Pakistan Journal of Ophthalmology, 2021)
This paper discusses how COVID-19 affected ophthalmology practices at JPMC and the measures taken to minimize the spread of infection among doctors, nurses, administrative staff, and patients. Staff members and doctors were divided into groups consisting of a consultant, two trainees, a house-officer and eight paramedics. Out of the eight paramedics, three were posted in theatre, two inwards and the remaining in outpatient clinics. These measures helped us in the restoration of our services quickly. All elective surgeries were cancelled. In the ward, social distancing was observed. No one was allowed inside the ward without thermal scanning. Only one attendant was allowed with pediatric patients and all the adults, including patient were required to wear masks. Before admitting patients to the ward, a negative COVID-19 PCR test was compulsory. These precautionary measures helped to reduce the spread of coronavirus among the department staff.